Complete Chromosome-scale genome sequence resource for sporisorium panici-leucophaei, the causal agent of sourgrass smut disease - Crestana, Gustavo Schiavone; Taniguti, Lucas Mitsuo; Dos Santos, Clesivan Pereira; Benevenuto, Juliana; Ceresini, Paulo Cezar [UNESP]; Carvalho, Giselle; Kitajima, João Paulo; Monteiro-Vitorello, Claudia Barros (Scientific Societies, 2021)
Here, we present the first complete chromosome-level genome assembly of the smut fungus strain Sporisorium panici-leucophaei SPL10A, the causal agent of the sourgrass (Digitaria insularis) smut disease. Combining Illumina paired-end and Nanopore long reads, we generated a final assembly composed of 23 chromosomes (22 nuclear and one mitochondrial) with 18,915,934 bp. Gene prediction accomplished using extrinsic evidence from the sugarcane smut fungus Sporisorium scitamineum originated a total of 6,402 protein-encoding genes. The secretome (388 proteins) and the effectorome repertoires (68 candidates) were also predicted, given their crucial roles in plant-pathogen interactions. The complete telomere-to-telomere chromosome sequences of this poorly studied fungus will provide a valuable resource for future comparative genomic studies among smuts to unravel their underlying pathogenicity mechanisms.
Keywords: Genome assembly; Nanopore sequencing; Plant-pathogen interaction; Smut fungi; Sporisorium scitamineum